Effect of Education Level, Personal Income, and Accessibility of Banking Services on Personal Financial Management among Working Women in West Java - Haruni Ode; Ahmad Junaidi; Sri Wahyuningsih; Saparman Saparman (Westscience Press, 2024)
This quantitative study examines the influence of education level, personal income, and accessibility of banking services on personal financial management practices among working women in West Java, Indonesia. Data were collected from a sample of 180 working women using structured questionnaires and analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS) 3. The findings reveal significant positive relationships between education level, personal income, accessibility of banking services, and personal financial management practices. Moreover, banking services accessibility partially mediates the relationships between education level and personal financial management and between personal income and personal financial management. These results underscore the importance of financial literacy, economic empowerment, and access to formal financial services in fostering financial well-being among working women in West Java. The study contributes to a deeper understanding of the socio-economic factors influencing personal financial management and informs evidence-based interventions to promote financial inclusion and gender equity in the region.